The Influence of Eggshell Collage Making Activities on Fine Motor Development of Early Childhood with Special Needs - Ariasih, Putu Novi; Ujianti , Putu Rahayu (Mimbar Ilmu, 2024)
Activities that can stimulate children's fine motor skills in inclusive schools have not been implemented optimally by teachers. Therefore, this research aims to prove the effect of the activity of making collages from egg shells on the fine motor development of young children with special needs. This type of research is experimental research, with the pre-experimental design method using a one group pretest-posttest design research design. The research population is early childhood children with special needs in class 1 and class 2. Sampling was carried out using a purposive sampling technique. The research sample consisted of two classes with a total sample of 5 children. Data collection methods are observation and documentation methods. The research instrument uses observation guidelines and documentation checklist sheets. Data analysis techniques, statistical methods, descriptive analysis and inferential statistics. The results of research hypothesis testing were carried out using the paired sample t-test which showed that the sig. (2-tailed) < 0.05 (0.01 < 0.05). So it can be concluded that there is a significant influence from the activity of making collages from egg shells on the fine motor development of young children with special needs. It is hoped that the implications of this research will be a reference for activities to develop students' fine motor skills.